2019
DOI: 10.1002/stem.2987
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Expression Marks Castration-Resistant Progenitor Cells in the Adult Murine Prostate

Abstract: Identification of defined epithelial cell populations with progenitor properties is critical for understanding prostatic development and disease. Here, we demonstrate that Sox2 expression is enriched in the epithelial cells of the proximal prostate adjacent to the urethra. We use lineage tracing of Sox2-positive cells during prostatic development, homeostasis, and regeneration to show that the Sox2 lineage is capable of self-renewal and contributes to prostatic regeneration. Persisting luminal cells express So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
2
18
1
Order By: Relevance
“…RUNX1-expressing cells often co-expressed TROP2 ( Figure 2E ), known to be widely expressed in castrated prostate epithelium ( Goldstein et al, 2008 ; Wang et al, 2007 ). Several castration-resistant luminal populations have been identified in mice ( Barros-Silva et al, 2018 ; Kwon et al, 2016 ; McAuley et al, 2019 ; Tsujimura et al, 2002 ; Wang et al, 2015 ; Wang et al, 2009 ; Yoo et al, 2016 ), including rare castration-resistant Nkx3-1 -expressing cells (CARNs). Accordingly, we observed low, but detectable, levels of NKX3.1 in some luminal cells, but only occasional RUNX1 + NKX3.1 + luminal cells in the distal regions of the castrated prostate ( Figure 2D ; Figure 2—figure supplement 1B,C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RUNX1-expressing cells often co-expressed TROP2 ( Figure 2E ), known to be widely expressed in castrated prostate epithelium ( Goldstein et al, 2008 ; Wang et al, 2007 ). Several castration-resistant luminal populations have been identified in mice ( Barros-Silva et al, 2018 ; Kwon et al, 2016 ; McAuley et al, 2019 ; Tsujimura et al, 2002 ; Wang et al, 2015 ; Wang et al, 2009 ; Yoo et al, 2016 ), including rare castration-resistant Nkx3-1 -expressing cells (CARNs). Accordingly, we observed low, but detectable, levels of NKX3.1 in some luminal cells, but only occasional RUNX1 + NKX3.1 + luminal cells in the distal regions of the castrated prostate ( Figure 2D ; Figure 2—figure supplement 1B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite being mostly quiescent under homeostatic conditions, the prostate gland encompasses incredible plasticity. In mice, surgical castration-induced prostate involution has proven an invaluable tool to identify progenitor castration-resistant cell populations, characterized by their ability to survive in the absence of androgens, and to fully regenerate an intact adult prostate after re-administration of testosterone ( Barros-Silva et al, 2018 ; Kwon et al, 2016 ; McAuley et al, 2019 ; Tsujimura et al, 2002 ; Wang et al, 2015 ; Wang et al, 2009 ; Yoo et al, 2016 ). Such plasticity has also been shown in defined experimental conditions to stimulate regenerative properties of epithelial subpopulations, including transplantations ( Barros-Silva et al, 2018 ; Burger et al, 2005 ; Lawson et al, 2007 ; Lukacs et al, 2010 ; Richardson et al, 2004 ; Wang et al, 2009 ; Xin et al, 2005 ; Yoo et al, 2016 ), injury repair ( Centonze et al, 2020 ; Horton et al, 2019 ; Kwon et al, 2014 ; Toivanen et al, 2016 ), and organoid assays ( Chua et al, 2014 ; Höfner et al, 2015 ; Karthaus et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we and others have identified a Sca-1 + Nkx3.1 − luminal cell population that resides at the mouse proximal prostatic ducts adjacent to the urethra. [18][19][20][21] We showed that these cells are not only phenotypically different from the Sca-1 − Nkx3.1 + luminal cells in the other anatomic regions in the mouse prostate but are also functionally distinct in that they possess a higher bipotent differentiation capacity. In this study, we examine their hierarchical relationships using a lineage tracing approach and determine the role of Sox2 in the maintenance and stem cell potential of the Sca-1 + luminal cells.…”
Section: Introductionmentioning
confidence: 81%
“…RUNX1 expressing cells often co-expressed TROP2 (Figure 2E), known to be widely expressed in castrated prostate epithelium (Goldstein et al, 2008;X.-D. Wang et al, 2007). Several castration-resistant luminal populations have been identified in mice (Barros-Silva et al, 2018;Kwon et al, 2016;McAuley et al, 2019;Tsujimura et al, 2002;B. Wang et al, 2015;X.…”
Section: Runx1 Expressing Cells Are Enriched In the Castrated Prostatmentioning
confidence: 97%
“…Despite being mostly quiescent under homeostatic conditions, the prostate gland encompasses incredible plasticity. In mice, surgical castration-induced prostate involution has proven an invaluable tool to identify progenitor castration-resistant cell populations, characterized by their ability to survive in the absence of androgens, and to fully regenerate an intact adult prostate after re-administration of testosterone (Barros-Silva et al, 2018;Kwon et al, 2016;McAuley et al, 2019;Tsujimura et al, 2002;B. Wang et al, 2015;X.…”
Section: Introductionmentioning
confidence: 99%